Predictive factors for the development of brain metastases in patients with malignant melanoma: a study by the Anatolian society of medical oncology - DANE, FAYSAL (SPRINGER, 2014)
The development of brain metastases (BMs) was associated with poor prognosis in melanoma patients. Patients with BMs have a median survival of < 6 months. Melanoma is the third most common tumor to metastasize to the brain with a reported incidence of 10-40 %. Our aim was to identify factors predicting development of BMs and survival. We performed a retrospective analysis of 470 melanoma patients between 2000 and 2012. The logistic regression analyses were used to identify the clinicopathological features of primary melanoma that are predictive of BMs development and survival after a diagnosis of brain metastases. There were 52 patients (11.1 %) who developed melanoma BMs during the study period. The analysis of post-BMs with Kaplan-Meier curves has resulted in a median survival rate of 4.1 months (range 2.9-5.1 months). On logistic regression analysis site of the primary tumor on the head and neck (p = 0.002), primary tumor thickness (Breslow > 4 mm) (p = 0.008), ulceration (p = 0.007), and pathologically N2 and N3 diseases (p = 0.001) were found to be significantly associated with the development of BMs. In univariate analysis, tumor thickness and performance status had a significant influence on post-BMs survival. In multivariate analysis, these clinicopathologic factors were not remained as significant predictive factors. Our results revealed the importance of primary tumor characteristics associated with the development of BMs. Ulceration, primary tumor thickness, anatomic site, and pathologic a parts per thousand yenN2 disease were found to be significant predictors of BMs development.
Keywords: Melanoma; Brain metastases; Predictive factors; CENTRAL-NERVOUS-SYSTEM; CEREBRAL METASTASES; CUTANEOUS MELANOMA; PROGNOSTIC-FACTORS; THERAPY; SURVIVAL; LYMPHADENECTOMY; FEATURES; TRIAL; STAGE